Medical Education Online: a case study of an open access journal in health professional education - D.J. Solomon (Information Research: An International Electronic Journal)
Introduction. The development of the World Wide Web (WWW) has made it possible of small groups of colleagues or even single individuals to create peer-reviewed scholarly journals. This paper discusses the development of Medical Education Online (MEO) an open access peer-reviewed journal in health professional education. Description. MEO was first published in April 1996 partly as an experiment and partly out of frustration with existing options for publishing in health professional education. The journal a forum for disseminating information on educating physicians and other health professionals and contains a variety of material including a peer-reviewed journal. The case study discusses the process of establishing the journal, the development of the journal over time, its struggle coping with an increasing number of submissions, review procedures, journal management software, indexing and archiving issues, journal policies, and access statistics. Conclusion. . MEO is one of many examples of successful small open access journals that operate largely on volunteer effort and are providing a useful niche in scholarly publishing.